PENYULUHAN PATOLOGI SOSIAL MASYARAKAT DESA - Fathur Rohman (Jurnal Bimbingan Penyuluhan Islam, 2021)
ABSTRACT Social pathology is a scientific discipline that discusses social symptoms that are considered sick, caused by social factors, so it is called the science of social disease, meaning that all human behavior that is considered inappropriate or violates general norms and customs or is not integrated with general behavior. As explained by Kartini Kartono, that two centuries before the 19 th and 20th centuries, social pathology had not yet emerged as a scientific discipline, because it did not yet have a specific style or style in conducting studies. According to the theory of pathology, society is always in a state of illness or a society that does not function in part or in whole. Meanwhile, according to the term pathology is a branch of the field of medicine that is concerned with the characteristics and development of disease through analysis of changes in function or state of body parts.